Analysis of the Principles of Ushul Fiqh in Addressing the Acceleration of Innovation in Sharia-Compliant Digital Economic Products - Hasir Budiman Ritonga; Amrin Borotan; Ahmad Rofi'i Harahap (Islamic Circle, 2026)
The innovation of digital economic products such as sharia e-wallets and sharia crowdfunding presents methodological challenges to the contemporary Islamic legal framework. This research aims to analyze the application of Ushul Fiqh principles as evaluative instruments for the dynamics of digital economic product innovation in Indonesia. The research method employed is qualitative with a normative-juridical approach and library research. The results indicate that the principle of al-ashl fi al-mu’amalah al-ibahah provides a space for legalizing technological innovation, while the principles of sadd al-dzari’ah and Maqasid Syari'ah function as risk mitigation instruments against gharar and speculation. The analysis of sharia e-wallets and crowdfunding suggests that sharia compliance relies not only on the formality of contracts but also on the accountability of fund management and consumer protection (hifdz al-maal). This study concludes that synergy between contemporary ijtihad, cross-disciplinary collaboration (fiqh experts, technologists, and economists), and the active role of fatwa institutions (DSN-MUI) is crucial in creating a harmonious, transparent, and equitable digital ecosystem.